Government Instruments and Challenges in the Free Nutritious Meal Program (MBG) in Bandung City - Agustini, Indah Trie Wahyuni; Deliarnoor, Nandang Alamsah; Kartini, Dede Sri (Journal of Local Government Issues, 2025)
This study analyzes government instruments and the challenges in implementing the Free Nutritious Meal Program (MBG) in Bandung City (2024-2025). The program faces several obstacles, including limited budgets, logistical and distribution constraints, low capacity of third-party providers, inadequate facilities and personnel, as well as weak supervision, coordination, socialization, and regulatory uniformity. Using a qualitative case study approach, data were collected through purposive sampling, observation, interviews, documentation, and triangulation, and analyzed using reduction, display, and conclusion-drawing techniques. The analysis applies Hughes’ (2012) framework of government instruments: provision, subsidy, production, and regulation. The findings show that the application of government instruments in the MBG program remains suboptimal. Among the four instruments, only subsidy functions relatively effectively, while provision, production, and regulation are still constrained. To address these challenges, the Bandung City Government is advised to strengthen budget flexibility, cross-sectoral logistics, and processing facilities in priority areas, while improving target mapping, facility audits, hygiene training, food quality monitoring, and standardized technical guidelines.